The Influence of Self Check-in Machine Performance, Adoption Behavior, And Perception of Ease on Decisions to Use Self Check-In Machines Through Consumer Communication at Terminal 3 Domestic Soekarno Hatta International Airport - Candra Ananda; Lira Agusinta; Jermanto Setia Kurniawan (Dinasti Review, 2025)
This research is motivated by the implementation of Self check-in at Terminal 3 Domestic Soekarno Hatta Airport, but along with the implementation there are still some shortcomings of Self check-in kiosks, including that they can only be used by passengers who do not have luggage and can only be used no later than 1 hour before departure. This study aims to determine the effect of Self check-in machine facility performance, adoption behavior, and perception of ease on the decision to use the self checkin machine through consumer communication at Terminal 3 Domestic Soekarno Hatta International Airport. The research method uses quantitative samples and research of 250 respondents taken using purposive sampling techniques. While the data collection technique uses questionnaires and data analysis using Structural Equation Modeling (SEM) based on Smart PLS. The results of the study show that consumer communication is influenced by the performance of Self check-in machine facilities, adoption behavior and perception of ease, and usage decisions. Furthermore, adoption behavior and perception of ease have a direct or indirect effect through consumer communication variables on the decision to use the Self check-in machine. However, consumer communication is not a variable that connects the influence of Self check-in machine performance on the decision to use the Self check-in machine.